Bioefficacy evaluation of ferrocenyl chalcones against Meloidogyne incognita and Sclerotium rolfsii infestation in tomato. Issue 3 (4th March 2022) - Yadav, Dinesh K.; Kaushik, Parshant; Tripathi, Kailash Pati; Rana, Virendra S.; Yeasin, Md; Kamil, Deeba; Pankaj,; Khatri, Dilip; Shakil, Najam A.
Abstract: The present study reports, bioefficacy evaluation of effective compounds against Meloidogyne incognita and Sclerotium rolfsii in pot cultured tomato. The identified five most effective compounds, i.e. (2 E )-1-(4-Methylphenyl)-3-ferrocenyl-prop-2-en-1-one (6g ), (2 E )-1-(4-Methoxyphenyl)-3-ferrocenyl-prop-2-en-1-one (6h ), (2 E )-1-(3-Bromophenyl)-3-ferrocenyl-prop-2-en-1-one (6j ), (2 E )-1-(2, 4-Dichlorophenyl)-3-ferrocenyl-prop-2-en-1-one (6k ) and (2 E )-1-(3, 5-Dichloro-2-hydroxyphenyl)-3-ferrocenyl-prop-2-en-1-one (6p ) along with Carbofuran 3G as positive control were tested at 20, 40 and 80 ppm by soil drenching and root dipping methods. The study revealed that all plant growth parameters were positively influenced by these compounds. The presence of an electron releasing group positively influenced the efficacy, and the activity was highest in compounds 6g and 6h at 80 ppm. Based on in vitro results against S. rolfsii, (2 E )-1-Ferrocenyl-3-(4-bromophenyl)-prop-2-en-1-one (3b ), (2 E )-1-Ferrocenyl-3-(2, 6-dichlorophenyl)-prop-2-en-1-one (3o ) and (2 E )-1-(5-Chloro-2-hydroxyphenyl)-3-ferrocenyl-prop-2-en-1-one (6o ) along with Tebuconazole 25.9% EC and Hexaconazole 5% SC as positive control were evaluated. The shoot length was found to be highest (24.50 cm) in plants treated with 3b followed by 3o and 6o at 1000 ppm. The percent disease incidence was significantly decreased as compared to control. The percent disease incidence was found to be minimum in plants treated with 3b at 1000 ppm. However, root dipping was not as effective as soil drenching. Therefore, ferrocenyl chalcone derivatives proved to be of great fungicidal and nematicidal potential opening new opportunities for expanding their effectiveness as new pest control agents.